2019
DOI: 10.1002/jsfa.9550
|View full text |Cite
|
Sign up to set email alerts
|

Twenty‐five years of total antioxidant capacity measurement of foods and biological fluids: merits and limitations

Abstract: This review summarises 25 years of investigations on antioxidants research in foods and biological fluids and critically analyses the merits and limitations of using the total antioxidant capacity (TAC) measurement in the metabolomic era. An enormous bulk of knowledge was produced regarding the antioxidant capacity of foods and large TAC databases were developed. A direct link between a food TAC value and any health benefit is erroneous and has led to several cases of consumer deception. However, the striking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(80 citation statements)
references
References 160 publications
(279 reference statements)
0
78
1
1
Order By: Relevance
“…With regard to nutrient antioxidant biomarkers, high P-NEAC as FRAP was associated with high levels of almost all antioxidants, including TP. While this marker seems to not reflect the amount of phenolic compounds contained in food [45], we observed positive associations between all P-NEAC assays and TP. D-NEAC was also positively associated with dietary intake (all carotenoids and flavonoids) and plasma antioxidant levels (lutein and α-tocopherol) in a study of 60 healthy non-smoking subjects [3].…”
Section: Dietary/plasma Neac Associations With Nutrient/inflammation contrasting
confidence: 78%
See 2 more Smart Citations
“…With regard to nutrient antioxidant biomarkers, high P-NEAC as FRAP was associated with high levels of almost all antioxidants, including TP. While this marker seems to not reflect the amount of phenolic compounds contained in food [45], we observed positive associations between all P-NEAC assays and TP. D-NEAC was also positively associated with dietary intake (all carotenoids and flavonoids) and plasma antioxidant levels (lutein and α-tocopherol) in a study of 60 healthy non-smoking subjects [3].…”
Section: Dietary/plasma Neac Associations With Nutrient/inflammation contrasting
confidence: 78%
“…D-NEAC has been associated with health outcomes in several epidemiological studies [44]. However, it has been argued that the in vitro antioxidant capacity may not reflect the real in vivo antioxidant potential of the body [2,5,45]. Studies assessing the relationship between D-NEAC and P-NEAC have reported, at best, moderately-weak correlations for some NEAC assays [4,14,15], while others did not support a correlation [46].…”
Section: D-neac and P-neac Relationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two ions with m/z 259 and 259.1 assigned to ABTS •+ degradation products were detected as well. The two adducts of the catechin/ABTS •+ reaction had m/z values of 803 and 560, the coupling reaction product (10) and hydrazinediylidene-like derivative (12), respectively (Figure 5b). Small amounts of the imine-like adduct (11) were also presumably detected on the preparative HPLC chromatogram, but its quantity was not enough for characterization.…”
Section: Reaction Pathways With Adducts Formationmentioning
confidence: 99%
“…Total antioxidant capacity (TAC) includes the synergic and redox interactions between the different molecules present in foods and biological fluids [16]. However, the results regarding TAC are not clear; in some studies, TAC was increased [6,14], but in other studies, TAC was decreased in PMW [11,13,15,17].…”
Section: Introductionmentioning
confidence: 99%